An Industrial-Archaeological Approach to the Mineral Loading Docks in Rande Strait, North-Western Spain. (2nd January 2017) - Pozo-Antonio, José Santiago; Pérez-Rey, Ignacio; Rial, Gonzalo
Abstract : During the 20th century, the need for raw material promoted a commercial transportation trade of iron ores from the deposits in north-western Spain, where Vigo city was considered one of the most important ports. The global energy crisis in the 1970s, as well as the strong competition from other exporting countries, dented the prolific activity of companies dedicated to the extraction and trading of iron ore. The main goal of this article is the evaluation of one particular element of the mining and industrial heritage — two old mineral loading docks in Ría de Vigo in the Rande Strait, linking the municipalities of Redondela and Moaña. Their development as a tourist resource would add to the cultural and economic activities already developed in the area.